Major Complication Following Kawasaki Disease in an Infant—The Development of Apical Infarction and Aneurysm Formation - Samuel Menahem (MDPI AG, 2021)
Considerable advances have occurred in the understanding of Kawasaki disease, with a substantial drop in morbidity and mortality following the infusion of gamma globulin during the acute phase. Nevertheless, major complications may still occur. A 27-year-old male presented as an infant of 11 weeks when he was diagnosed as having Kawasaki disease. He was appropriately treated with aspirin and a gamma globulin infusion following his diagnosis 5 days after the onset of his illness. Despite that, he went on to develop coronary aneurysms. He represented a few weeks later with a history of inconsolable crying associated with pallor, suggestive of ischaemic chest pain. A repeat echocardiogram revealed infarction of the apex of the left ventricle with localised thrombus formation. There were persistent aneurysms within both coronary artery systems. A further infusion of gamma globulin was given. In view of the thrombus formation, he was started on warfarin. The thrombus gradually resolved with the development of a clearly defined left ventricular apical aneurysm. He has remained on warfarin, aiming for an international normalised ratio (INR) level of 2 to 2.5. He developed mild left ventricular dysfunction during late childhood, which improved following the commencement of an angiotensin-converting enzyme (ACE) inhibitor. Despite his ventricular aneurysm, there has been no documented evidence of ventricular tachycardia over the years. Repeated testing initially by nuclear perfusion scans and then by stress echocardiograms failed to show any inducible ischaemia apart from the apical ventricular aneurysm. A recent computed tomography (CT) coronary angiogram revealed an ectatic origin of the left main and the right coronary arteries with mild calcification involving the mid-portion of the latter and slight calcification of the former. His raised cholesterol level has responded well to a statin. Despite the persistence of the ventricular aneurysm, he continues to be managed conservatively, as he has remained well. The question arises as to what the long-term implications are of his left ventricle apical aneurysm. Should it be excised? Is he at risk for ventricular tachycardia and sudden death? In addition, although the coronary aneurysms have resolved, the CT coronary angiogram shows calcium plaques in both coronary arteries at the site of the earlier aneurysms. This finding raises the question as to whether all children who develop coronary artery aneurysms following Kawasaki disease should have a CT coronary angiogram performed in adulthood.